2019
DOI: 10.3390/atmos10110681
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Continental Mesoscale Convective Systems in Forecast Busts within Global Weather Prediction Systems

Abstract: Despite significant, steady improvements in the skill of medium-range weather predictionsystems over the past several decades, the accuracy of these forecasts are occasionally very poor.These forecast failures are referred to as “busts” or “dropouts”. The lack of a clear explanationfor bust events limits the development and implementation of strategies designed to reduce theiroccurrence. This study seeks to explore a flow regime where forecast busts occur over Europe inassociation with mesoscale convective sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Given the role of MCS in generating forecast errors in global models (e.g., Lillo & Parsons, 2017;Parsons, Lillo, et al, 2019;Rodwell et al, 2013Rodwell et al, , 2018 capturing the mechanisms that determine the nature and maintenance of MCS in weather and climate models deserves significant attention. Nocturnal convection, in particular, has poor predictive skill (e.g., Geerts & co-authors, 2017).…”
Section: 1029/2019jd032279mentioning
confidence: 99%
“…Given the role of MCS in generating forecast errors in global models (e.g., Lillo & Parsons, 2017;Parsons, Lillo, et al, 2019;Rodwell et al, 2013Rodwell et al, , 2018 capturing the mechanisms that determine the nature and maintenance of MCS in weather and climate models deserves significant attention. Nocturnal convection, in particular, has poor predictive skill (e.g., Geerts & co-authors, 2017).…”
Section: 1029/2019jd032279mentioning
confidence: 99%
“…This study suggests that users should access the forecast uncertainty using ensemble forecasts and the differences in forecasts among the NWP centers when forecasts are initialized on the GB and AC patterns, especially on AC pattern in recent years. For the European forecast busts, moist processes associated with warm conveyor belt (Grams et al, 2018) and mesoscale convection over North America (Parsons et al, 2019) contribute to the large errors. In addition, Day et al (2019) showed that the deterioration of the Arctic forecast reduces midlatitudes forecast skill during Scandinavian blocking episodes.…”
Section: Discussionmentioning
confidence: 99%
“…(2013), Lillo and Parsons (2017), and Parsons et al . (2019) provide results variously implicating mesoscale convective complexes (MCCs), coastal cyclogenesis, and tropical cyclone extratropical transition events. Other examples include Magnusson (2017) and Grams et al .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, some recent studies have implicated errors with respect to discrete, smaller-scale features as being the ultimate source of "busts" or "dropouts" in the large-scale forecast skill of state-of-the-art operational systems. For example, Rodwell et al (2013), Parsons (2017), andParsons et al (2019) provide results variously implicating mesoscale convective complexes (MCCs), coastal cyclogenesis, and tropical cyclone extratropical transition events. Other examples include Magnusson (2017) and Grams et al (2018), whose results point to individual synoptic features such as jet streaks, cyclogenesis events, and upper troughs.…”
Section: Introductionmentioning
confidence: 99%